ANALISIS STRATEGI PERUSAHAAN J&T EXPRESS DALAM MENINGKATKAN LOYALITAS KONSUMEN BERDASARKAN PERSPEKTIF BISNIS ISLAM - Jelita Eriyanti; Nini Sumarni (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This research aims to find out the strategies used by J&T Express Ampek Angkek to increase consumer loyalty and to find out the perspective of J&T Express Ampek Angkek's Islamic business perspective in increasing consumer loyalty. This research is a type of field research (Field Research), this research uses descriptive-qualitative methods , where in this research the researcher collected data by interviews, observations and documentation with SPV, employees and consumers of J&T Express Ampek Angkek. J&T Express Ampek Angkek used in increasing consumer loyalty is the 7P strategy (Product, Price, Promotion, Place, People/HR, Process and Physical Evidence). Products that can be picked up at the consumer's address without additional costs, reasonable prices 10,000-14,000 for delivery within the city and 52,000 for delivery outside the city, location selection is in a strategic area that is easy to reach and is located on the side of the main road, spacious parking and clean rooms , in terms of promotion, we have used various methods such as social media, exhibitions, prizes, have experienced and professional employees, and always provide loyalty to consumers